Analysis of The Effect of Work Environment and Compensation on Performance of Motorcycle Automotive Dealer Employees - Tama Krisnahadi; Wulandari; Anton; Iswahyuningsih; Dewi Ratih Kusuma Wardani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to examine how employee performance is impacted by the workplace and salary. The research subjects in this study are staff members of ine of motorcycle automotive dealer company in Indonesia. 30 employees made up the study's sample. In order to sample every employee in this workplace, nonprobibality sampling was utilized in this study along with saturated sampling categories. Using a questionnaire, data was collected, and SPSS software was used to analyze it using multiple linear regression analysis models. The findings of this study suggest that employee performance is influenced by both the workplace and salary. Employee performance is affected in part by both the work environment and remuneration. Employee performance may be described by the workplace and compensation, according to the Adjusted R Square value of 0.88, and the remaining can be accounted for by factors beyond the scope of this research.